O03-5 Sickness absence changes in the EU-27 by welfare regime during a turbulent decade. (1st September 2016) - Whitworth, Ryan; Gimeno, David
Abstract : Objectives: Sickness absence is a global health indicator of working populations and may be a useful indicator of how well a country is doing. We examine the changes in work-related sickness absence by national welfare typologies over the 2000s within the EU27 members. Methods: A representative sample of the EU27 active working population, aged 15–64 years, (n = 93, 740) from three waves of the European Survey on Working Conditions (2000, 2005, and 2010) was used. Outcomes were work-related sickness absence prevalence and median annual days absent, both total and from accidents at work. Poisson and median regression models were used to examine differences by welfare typology while controlling for covariates. Results: Scandinavian (58%) and Bismarckian (43%) typologies had the highest prevalence of sickness absence while Post-Communist (29%) and Former USSR (27%) were lowest, and Anglo-Saxon (39%) and Southern (36%) were in the middle. In 2005, prevalence dropped across all typologies but rose again in 2010 to levels mostly exceeding the start of the decade, resulting in a V-pattern. Amongst those with at least one day of sickness absence, the median annual days absent increased in 2005 but returned to similar or lower levels in most typologies in 2010, resulting in an inverse V-pattern (overall median days of 9 in 2000, 10 in 2005, and 7 in 2010). Absence due to accidents at work although of smaller proportion, followed a similar pattern. Throughout the 2000s, absolute prevalence of sickness absence and median days of sickness absence varied by welfare typology but relative risk patterns did not. Conclusions: We showed for the first time that there are differences by welfare typology within the EU27 members in both the magnitude of sickness absence prevalence and median days missed but that longitudinal patterns appeared similar during 2000s.